A Study of Some Socio-economic and Institutional Factors Affecting Beef Production in the Middle Belt of Nigeria. - Ige, Samuel Abayomi (Obafemi Awolowo University, 2014)
NIGERIA, like most developing nations of the world, faces acute short-age of animal protein intake. Beef production has been recognized as one of the means by which the level of consumption of animal protein can be increased. The main objective of this research therefore was to conduct an exploratory study into some socio-economic and institutional factors affecting beef production in the central region of Nigeria which offers the greatest potential for ruminant livestock production in the country.